(untitled) (Research, Society and Development, 2024)
Subgingival carious lesions can be restored with a deep margin elevation, which is performed with a resin composite, and then rehabilitated through a direct or indirect restoration, however, the limitations of this technique are not yet well specified, so as the material that allows adequate marginal adaptation and resistance to fracture. The objective of this article is to carry out a review of the literature that evaluates the appropriate materials to perform a deep margin lift and that allow adequate marginal adaptation, as well as studies that evaluate fracture resistance. Thus, a search was carried out in the scientific bases of PUBMED, SCOPUS, COCHRANE AND DIALNET, for articles in an interval of no more than 5 years, of which 12 were selected and analyzed in this study. The results of the qualitative analysis showed that resin composites modified with short fibers or hybrid nanofilled composites give good long-term results, although more in vivo studies are needed to give greater reliability to the technique.